USE OF AZOLLA (Azolla pinnata) MEAL AS A SUBSTITUTE FOR DEFATTED SOYBEAN MEAL IN DIETS OF JUVENILE BLACK TIGER SHRIMP (Penaeus monodon) - Agung Sudaryono (JOURNAL OF COASTAL DEVELOPMENT, 2006)
A 42-day feeding experiment was conducted to study the feasibility of utilizing azolla (Azollapinnata) meal (AZM) as a replacement for soybean meal (SBM) in the diets for juvenile Penaeusmonodon. The replacement levels of azolla meal protein in the diets were 0, 25, 50, 75, and 100% of thetotal soybean meal protein. All diets were isonitrogenous at 40% crude protein. Shrimp (mean initialweight, 0.49±0.02 g) were fed three times daily ad libitum at an initial feeding allowance of 10% totalbody weight per day. A completely randomized design was used in the study and shrimp were stocked ata density of 10 animals/72 L-tank in triplicates. There were not significant differences in weight gains(1.97-2.06 g), specific growth rates (SGR 3.81-3.89%/d), feed conversion ratios (FCR 2.06-2.77),protein efficiency ratios (PER 0.89-1.24), apparent protein utilization (APU, 43.3-56.7%), and survivalrates (99.1-100%) among shrimp groups (P>0.05). Feeding preference tests showed that either soybeanmeal-based diet or azolla meal-based diet was similarly preferred (P>0.05) by shrimp with thepreference values of 51 and 40% for soybean meal-based diet and azolla meal-based diet, respectively.The results of this study suggest that azolla meal protein can replace up to 100% of the soybean mealprotein in practical diet for juvenile black tiger shrimp Penaeus monodon under laboratory conditionswithout any adverse performance. The use of azolla meal as an alternative plant protein source tosoybean meal may be able to reduce the feed costs for Penaeus monodon aquaculture.